2007
DOI: 10.1111/j.1365-2958.2007.05807.x
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of iron homeostasis in Saccharomyces cerevisiae by high zinc levels: a genome‐wide study

Abstract: SummaryZinc is an essential metal that, when in excess, can be deleterious to the cell. Therefore, homeostatic mechanisms for this cation must be finely tuned. To better understand the response of yeast in front of an excess of zinc, we screened a systematic deletion mutant library for altered growth in the presence of 6 mM zinc. Eighty-nine mutants exhibited increased zinc sensitivity, including many genes involved in vacuolar assembling and biogenesis. Interestingly, a mutant lacking the Aft1 transcription f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

13
99
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(114 citation statements)
references
References 75 publications
13
99
2
Order By: Relevance
“…Deletion of some trafficking-related genes has been shown to result in sensitivity to zinc, calcium, or alkaline conditions (Serrano et al 2004;Sambade et al 2005;Pagani et al 2007). Our strategy for screening effectively detected reduced VATPase activity levels to $10% of wild-type yeast (scored as ,50% of activity in the vma21QQ mutant strain).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Deletion of some trafficking-related genes has been shown to result in sensitivity to zinc, calcium, or alkaline conditions (Serrano et al 2004;Sambade et al 2005;Pagani et al 2007). Our strategy for screening effectively detected reduced VATPase activity levels to $10% of wild-type yeast (scored as ,50% of activity in the vma21QQ mutant strain).…”
Section: Discussionmentioning
confidence: 99%
“…Genome-wide screens for zinc or calcium (at pH 7.5) sensitivity have found genes that do not directly contribute to V-ATPase function yet show sensitivity to excess metals (Sambade et al 2005;Pagani et al 2007). An example is deletion of the vacuolar zinc transporter Zrc1p, which confers zinc sensitivity even though vacuolar acidification is normal (data not shown).…”
mentioning
confidence: 99%
“…Several observations suggest that the uptake and homeostasis of iron and zinc, both essential elements but toxic at high cellular concentrations, are intertwined. Pagani et al (2007) reported the disruption of Fe homeostasis by high Zn. For instance, it was shown that Zn stress could induce the expression of several components of iron uptake (Fet3, Ftr1).…”
Section: Discussionmentioning
confidence: 99%
“…All organisms have therefore developed homeostatic mechanisms aimed to ensure the minimal zinc levels required for normal metabolism but also to avoid zinc intoxication (Pagani et al, 2007). O. maius Zn is a metal tolerant ericoid mycorrhizal isolate derived from roots of V. myrtillus growing in a heavy metal polluted site where zinc was the most abundant contaminant ( Martino et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…In plant cells, it was speculated that a vacuolar membrane transporter AtMTP1 would function in maintaining the subcellular zinc concentration for the ion homeostasis, suggesting that vacuoles are important organelles for tolerance to high zinc exposure (Kobae et al, 2004). In fact, in budding yeast, mutants in vacuolar organization are sensitive to high zinc concentration (Pagani et al, 2007). Based on this idea, although no obvious phenotype on vacuolar morphology was observed, possible perturbation in vacuolar function would induce the zinc sensitivity in single disruptants vsl1D and fsv1D.…”
Section: Discussionmentioning
confidence: 99%